Total Plate Count (TPC) Test and Contamination of Coliform Escherichia coli and Salmonella sp. Bacteria in Cucumulawak Jamu in Traditional Markets in Medan City - Tarisa Adma; Marlinda Nilan Sari Rangkuti (Biocaster : Jurnal Kajian Biologi, 2026)
Jamu is a traditional Indonesian drink derived from plants that are efficacious for use in efforts to maintain health and cure diseases. However, because the manufacturing process is still simple, jamu is at high risk of contamination by microorganisms such as fungi and pathogenic bacteria such as Escherichia coli and Salmonella sp. This study aims to determine the presence of Escherichia coli and Salmonella sp. Coliform contamination in Javanese turmeric herbal medicine sold in traditional markets. This study is based on the simple process of making jamu using hands, unclean clothes from jamu makers, and unclean processing areas, this will increase the risk of contamination and result in jamu being contaminated by microorganisms that can endanger consumer health. Data collection techniques use testing and counting of bacterial colonies with the TPC (Total Plate Count) method and Escherichia coli bacteria with the MPN (Most Probable Number) method which consists of presumptive test, confirmatory test and complementary test. The results of the analysis showed that in the TPC (Total Plate Count) test, three of the five samples, namely Sp 1, Sp 3, and Sp 4, showed results that were suitable for consumption because the TPC (Total Plate Count) value did not exceed the maximum limit of BPOM 2019 and two of the five samples, namely Sp 2 and Sp 5, showed results that were not suitable for consumption because they exceeded the maximum limit of BPOM 2019. These findings suggest that poor hygiene practices during jamu preparation can lead to contamination that threatens consumer health, emphasizing the need for improved sanitation control and standardized processing methods.